The hidden side of the cholo: Presence of cultural traits and affirmation of an identity - Cosamalón, Ana Lucía (1993)
In recent decades, Peruvian social sciences have highlighted the presence of a chola population, possessing a set of cultural traits that intervene powerfully in the life of the country, especially in Lima. In other words, the Chola population has peculiar political, economic, social and religious behaviors that show the existence of a culture within which positive values ​​nest that would be fundamental for the development of the Peruvian nation. Moreover, authors such as José María Arguedas, Aníbal Quijano and, lately, Carlos Franco and Carlos Iván Degregori are committed to the formation of a possible chola, mestizo identity, which they consider modern and democratic, important for the constitution of popular urban identities. .